Innovative entrepreneurship in the Republic of Kazakhstan: the role of the state in a forming of the institutional conditions for the development of innovative activity of enterprises - Stavbunik, Ye.A.; Nurmaganbetov, A.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article the participation of the state in the creation of institutional prerequisites that contribute to the development and revitalization of innovative business entities is considered. The definition of innovative entrepreneurship as a specific actor of innovative relations is given. Its internal characteristics are highlighted. We study the relationship of small, medium and large businesses to innovative processes. This is done on the basis of the proportion of innovatively active enterprises in Kazakhstan at the country level and in the regional context. The general and specific problems that hinder the innovation processes faced by enterprises of various sizes are described. It is noted that Kazakhstani businessmen to a greater extent demonstrate the imitative nature of production behavior, regardless of the scale of the enterprise, which carries out various types of innovation. It is also revealed that large companies are the most innovative in Kazakhstan, because they are largely provided with the necessary conditions for this. Several priority areas of state participation in terms of accelerating the development of innovation activities are highlighted. Proposals for improving public administration in the formation of institutional conditions for innovative entrepreneurship are made.